234k views
16 votes
 Shauna solve the polynomial equations given in the table determine whether each polynomial is correct select correct or incorrect for each equation

 Shauna solve the polynomial equations given in the table determine whether each-example-1
User Ghayel
by
5.7k points

2 Answers

12 votes

Answer:

correct / incorrect / incorrect

Explanation:

5a - 8 + 2a² + 2a - 1 ← collect like terms

= 2a² + 7a - 9 ← correct

-------------------------------------

b² + 6b - 4 - (3b + b²) ← distribute parenthesis by - 1

= b² + 6b - 4 - 3b - b² ← collect like terms

= 3b - 4 ≠ 2b² + 3b - 4

---------------------------------------

9c - 4c² - (2c² + c) ← distribute parenthesis by - 1

= 9c - 4c² - 2c² - c ← collect like terms

= - 6c² + 8c ≠ - 6c² + 10c

User AidinMC
by
5.0k points
11 votes

Answer:

correct

incorrect

incorrect

Explanation:


\begin{aligned}(5a-8)+(2a^2+2a-1)&=5a-8+2a^2+2a-1\\& = 2a^2+5a+2a-8-1\\ & = 2a^2+7a-9\end{aligned}


\implies (5a-8)+(2a^2+2a-1)=2a^2+7a-9\quad\textsf{is correct}

---------------------------------------------------------------------------------------


\begin{aligned}(b^2+6b-4)-(3b+b^2) &=b^2+6b-4-3b-b^2\\ & = b^2-b^2+6b-3b-4\\& = 3b-4\end{aligned}


\implies (b^2+6b-4)-(3b+b^2)=2b^2+3b-4\quad\textsf{is incorrect}

---------------------------------------------------------------------------------------


\begin{aligned}(9c-4c^2)-(2c^2+c) &=9c-4c^2-2c^2-c\\ & = -4c^2-2c^2+9c-c\\& = -6c^2+8c\end{aligned}


\implies (9c-4c^2)-(2c^2+c)=-6c^2+10c\quad\textsf{is incorrect}

User Butallmj
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.